Length of Stay Among Schizophrenia Patients in Referral Health Facilities 2023: Kaplan-Meier and Cox Analysis - Saefurrohim, Muhamad Zakki; Putri Rahayu , Eka; Ariyanti, Rea; Putri Rahayu , Agustin; Pratomo , Hadi (Jurnal Jaminan Kesehatan Nasional, 2025)
Schizophrenia contributes significantly to global disease burden, with hospitalization management being crucial for treatment outcomes. This study aimed to determine factors influencing length of stay and recovery outcomes among schizophrenia patients in Indonesian referral health facilities. Secondary data analysis was conducted using BPJS Kesehatan sample data from 2023. Of 54,820 mental health records, 2,562 schizophrenia patients treated at referral facilities were analyzed. Cox proportional hazards regression was used to identify factors associated with discharge status, while Kaplan-Meier analysis examined length of stay distribution. Mean length of stay was 19.9 days. Significant factors associated with better recovery outcomes included: treatment at general hospitals (HR=2.31, p<0.001), public hospitals (HR=0.57, p<0.001), undifferentiated (HR=1.45, p<0.001) and catatonic schizophrenia subtypes (HR=1.70, p=0.029), single medical procedure (HR=0.73, p<0.001), and local treatment facilities (HR=1.42, p=0.028). Healthcare service factors and clinical characteristics significantly outweigh demographic factors in determining recovery outcomes. These findings emphasize the importance of healthcare service quality and accessibility in schizophrenia treatment, supporting integrated care models and universal healthcare access policies.